Comparative study of the effect of flame retardants on the ignition temperature of epoxy composites; Eurasian Physical Technical Journal; Vol. 18, No. 2 - Amelkovich Yu. A. Yuliya Alexandrovna; Nazarenko O. B. Olga Bronislavovna; Smirnova I. N. Irina Nikolaevna; Zadorozhnaya T. A. Tatiyana Anatolyevna (2021, 2021)
Title screen